ASSOCIATION OF DIETARY PATTERNS AND GESTATIONAL DIABETES MELLITUS WITH ANEMIA AMONG PREGNANT PAKISTANI WOMEN: A CROSS - SECTIONAL STUDY (The Research of Medical Science Review, 2025)
AIMS: The purpose of this study is to investigate the relationship between dietary habits and the prevalence of anemia and Gestational Diabetes Mellitus (GDM) in Pakistani pregnant women.MATERIALS AND METHODS: A cross-sectional study was conducted on 178 pregnant Women who attended prenatal clinics at various hospitals in different regions of Pakistan. A validated food frequency questionnaire (FFQ) was used to assess dietary intake. Gestational Diabetes Mellitus was diagnosed using the International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria, while anemia was diagnosed with World Health Organization (WHO) guidelines.RESULT: The Chi-squared (p<0.05) test was used to investigate the relationships between anemia, GDM, and dietary habits. The prevalence of anemia was 108 (60.6%) among the participants, with 58 (32.5%) classified as having mild anemia, 34 (19.10%) as moderate and 16 (8.9 %) as severe anemia. In contrast, 70 (39.3%) were non-anemic. The prevalence of GDM in Pakistani women was 18 (10.1%), while 160 (89.8%) did not have GDM. A diet high in carbohydrates and low in fruits and vegetables was significantly linked to increased prevalence rates of anemia and GDM.CONCLUSION: The study emphasizes the importance of dietary habits in the development of GDM and anemia in pregnant Pakistani women. A diet high in carbohydrates and low in essential nutrients is one of the main risk factors for these conditions. These findings highlight the need for dietary modifications and nutritional education to promote better eating practices among pregnant Pakistani women.